2016
DOI: 10.5713/ajas.16.0279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and freezing/thawing sequence on quality attributes of bovine Mm. gluteus medius and biceps femoris

Abstract: ObjectiveThe effects of aging and freezing/thawing sequence on color, physicochemical, and enzymatic characteristics of two beef muscles (Mm. gluteus medius, GM and biceps femoris, BF) were evaluated.MethodsBeef muscles at 3 d postmortem were assigned to four different combinations of aging and freezing/thawing sequence as follows; aging at 2°C for 3 wk (A3, never-frozen control), freezing at −28°C for 2 wk then thawing (F2, frozen/thawed-only), aging at 2°C for 3 wk, freezing at −28°C for 2 wk then thawing (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…For each beef cut, both wet and dry aging processes led to reduction in shear force (p<0.05). Meat is tenderized by proteolytic enzymes, which degrade myofibrillar and cytoskeletal proteins that weaken the muscle structure and increase tenderness during wet and dry aging ( Kim et al, 2017 ; Oh et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each beef cut, both wet and dry aging processes led to reduction in shear force (p<0.05). Meat is tenderized by proteolytic enzymes, which degrade myofibrillar and cytoskeletal proteins that weaken the muscle structure and increase tenderness during wet and dry aging ( Kim et al, 2017 ; Oh et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The a* and b* values of the rump were not significantly affected by aging or the aging method. Color stability can be affected by muscle types, which have different oxygen consumption rates and metmyoglobin reductase activities ( Kim et al, 2017 ). In the present study, color change was dependent on aging method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results showed that the decrease of WHC among the three groups was significantly different in the same storage period. Different formation rate of ice crystal and level of protein oxidation caused by various temperature might explain these differences (Kim & Kim, 2017). Therefore, storage temperature, storage time, and their interaction had a significant effect on WHC (p < .05).…”
Section: Water-holding Capacity (Whc)mentioning
confidence: 96%
“…Wet-aging improves the tenderness of meat as a part of the proteolytic degradation of the myofibrillar protein and increases the flavor of aged meat because of the changing sequence of peptides and amino acids [ 8 , 9 ]. It also increases the eating quality of meat at different storage times and processes [ 10 ]. On the other hand, the taste, flavor, texture, and other physicochemical characteristics of aged-meat varies according to the different meat cuts because of the different contents of collagen, free amino acids, fatty acids, and nucleotides [ 11 ].…”
Section: Introductionmentioning
confidence: 99%